Layer-specific systolic and diastolic strain in hypertensive patients with and without mild diastolic dysfunction. Issue 1 (March 2018) - Sharif, Hisham; Ting, Stephen; Forsythe, Lynsey; McGregor, Gordon; Banerjee, Prithwish; O'Leary, Deborah; Ditor, David; George, Keith; Zehnder, Daniel; Oxborough, David
Abstract : This study sought to examine layer-specific longitudinal and circumferential systolic and diastolic strain, strain rate (SR) and diastolic time intervals in hypertensive patients with and without diastolic dysfunction. Fifty-eight treated hypertensive patients were assigned to normal diastolic function (NDF, N  = 39) or mild diastolic dysfunction (DD, N  = 19) group. Layer-specific systolic and diastolic longitudinal and circumferential strains and SR were assessed. Results showed no between-group difference in left ventricular mass index (DD: 92.1 ± 18.1 vs NDF: 88.4 ± 16.3; P  = 0.44). Patients with DD had a proportional reduction in longitudinal strain across the myocardium (endocardial for DD −13 ± 4%; vs NDF −17 ± 3, P  < 0.01; epicardial for DD −10 ± 3% vs NDF −13 ± 3%, P  < 0.01; global for DD: −12 ± 3% vs NDF: −15 ± 3, P  = 0.01), and longitudinal mechanical diastolic impairments as evidenced by reduced longitudinal strain rate of early diastole (DD 0.7 ± 0.2 L/s vs NDF 1.0 ± 0.3 L/s, P  < 0.01) and absence of a transmural gradient in the duration of diastolic strain (DD endocardial: 547 ± 105 ms vs epicardial: 542 ± 113 ms, P  = 0.24; NDF endocardial: 566 ± 86 ms vs epicardial: 553 ± 77 ms, P  = 0.03). Patients with DD also demonstrate a longer duration of early circumferential diastolic strain (231 ± 71 ms vs 189 ± 58 ms, P  = 0.02). In conclusion, hypertensive patients with mild DD demonstrate a proportional reduction in longitudinal strain across the myocardium, as well as longitudinal mechanical diastolic impairment, and prolonging duration of circumferential mechanical relaxation.